2006
DOI: 10.15288/jsa.2006.67.113
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute alcohol consumption, cognitive reserve, partner risk, and gender on sexual decision making.

Abstract: Objective-In past alcohol administration studies, intoxicated college students have been more willing to have unprotected sex with a hypothetical new partner than sober or placebo students. The objective of the present research was to extend past work by examining the effects of gender, cognitive reserve, and partner risk on intoxicated sexual decision making. Method-Before assigning participants (60 women and 60 men) to a drink condition, cognitive reserve was assessed with the reading subtest of the Wide Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 56 publications
1
43
3
2
Order By: Relevance
“…Finally, our biolgical sex findings were perfectly consistent with those observed in the other experiments (Abbey et al, 2005;Abbey, Saenz, Buck, Parkhill, & Hayman, 2006): Men reported higher risk-taking than women, and biolgical sex did not interact with alcohol. Compared to women, men's greater willingness to engage in risky sex has generally been attributed to their more liberal attitudes about casual sex (Oliver & Hyde, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, our biolgical sex findings were perfectly consistent with those observed in the other experiments (Abbey et al, 2005;Abbey, Saenz, Buck, Parkhill, & Hayman, 2006): Men reported higher risk-taking than women, and biolgical sex did not interact with alcohol. Compared to women, men's greater willingness to engage in risky sex has generally been attributed to their more liberal attitudes about casual sex (Oliver & Hyde, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…Leigh and Aramburu (1996) found that male participants were more sexually aroused throughout the given scenario and more likely to pursue sexual activity. In contrast, Abbey, Saenz, Buck, Parkhill, and Hayman (2006) did not find significant gender differences in terms of sexual arousal. In addition to gender, these scenario-based studies found other individual influences on one's alcohol-fueled sexual decision making: alcohol expectancies and sexual history (Abbey, Saenz, & Buck, 2005), as well as verbal skills and the riskiness of partnering with the opposite-gender character in the scenario (Abbey et al, 2006).…”
Section: Alcohol-fueled Sexual Decision Makingcontrasting
confidence: 73%
“…Meanwhile, we admit that there probably exist other individual difference factors related to alcohol expectancy effects and that may modulate the link between alcohol and memory (e.g. Abbey, 2006;Davis, Hendershot, George, Norris, & Heiman, 2007;Davis et al, 2010). Therefore, future studies should include questionnaires tapping not only alcohol-related expectancies (e.g.…”
Section: Discussionmentioning
confidence: 98%